Transformasi Pembelajaran di TPA Toriqul Huda melalui Pendekatan Modul Ajar dan Media Interaktif - Silvi, Annisa; Athiroh, Zuhriyyatul; Fa’iz, Nasywa; Astriyani, Sephia; Putri, Citra; Fauziyah, Fina; Dwi, Pursiati; Roofi, Putri; Nublah, Farah; Sandy, Ditta; Hanin, Aisyah (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The challenges encountered during the learning process at TPA Toriqul Huda encompass the lack of structured educational guidelines, reliance on conventional lecture approaches, and limited technological literacy among educators. This community service initiative seeks to address these issues through the development and application of instructional modules and interactive educational tools as pedagogical innovations. The implementation methodology comprises several phases: preparation and strategic planning, creation and proposal of teaching modules alongside interactive media, production and development of flipbook-based materials, practical implementation, and comprehensive evaluation. Findings reveal that the application of instructional modules and interactive media generated favorable outcomes for the educational process at TPA Toriqul Huda. Students demonstrated increased engagement, active participation, and improved comprehension of the presented material. Furthermore, educators received clear instructional frameworks for content delivery, resulting in more organized and systematic teaching-learning processes. Consequently, these pedagogical innovations hold promise as viable solutions for enhancing educational quality in TPA settings while fostering generations of morally upright individuals grounded in strong religious foundations.